Trends of lymphoma incidence in US veterans with rheumatoid arthritis, 2002–2017. Issue 2 (8th July 2020) - Singh, Namrata; Gao, Yubo; Field, Elizabeth; Link, Brian K; Weiss, Noel; Curtis, Jeffrey R; Lynch, Charles F; Vaughan-Sarrazin, Mary
Abstract : Objective: Past epidemiological studies have consistently demonstrated a link between rheumatoid arthritis (RA) and the incidence of lymphoma and it has been posited that high systemic inflammatory activity is a major risk determinant of lymphomagenesis. Given advances in the therapeutic armamentarium for RA management in recent years, the resulting lower level of disease activity could have led to a decline in lymphoma incidence in patients with RA. This study examined recent trends in lymphoma incidence in US veterans with RA. Methods: Patients with RA were identified in the Veterans Affairs (VA) Corporate Data Warehouse. Lymphoma incidence was identified through the end of 2018 from the VA Central Cancer Registry and compared among patients diagnosed during 2003–2005, 2006–2008, 2009–2011 and 2012–2014. Results: Among persons diagnosed with RA during 2003–2005, the incidence of lymphoma in the next 6 years was 2.0 per 1000 person-years. There was a steady decline in lymphoma incidence during the corresponding 6 years following diagnosis in the subsequent three cohorts, with a rate of 1.5 per 1000 person-years in the 2012–2014 cohort (incidence relative to that in the 2003–2005 cohort=0.79 (95% CI 0.58 to 1.1)). There was no similar decline in lymphoma incidence in VA patients diagnosed with osteoarthritis. Conclusion: We observed a decline in lymphoma incidence in recent years among American veterans with RA. Further studies are needed to evaluate the specific factors driving this decline.